Pregnancy Induced Hypertension among Pregnant Women in Dhaka City, Bangladesh (Medico Legal Update, 2021)
This cross-sectional study has been conducted in the Bangabandhu Sheikh Mujib Medical UniversityGynaecology and Obstetrics Division on 72 patients who have been admitted from December 2018 toMarch 2019, in order to find out the percentage of pregnancy-induced high blood pressure among pregnantmothers. Of the 72 patients, 25(34.7%) have been diagnosed with pre-eclamptictoxaemia 27(37.1%) inducedpregnancy and 20(27.8%) with eclampsia. Most people were 21-25 years old and their average age was 25.3years old. Of the 72 patients, 38 were primipara (52.8 percent). 20 (27.8%) of newborns were delivered before37 weeks, while 52 (72,2%) were delivered before 37 weeks. A cesarean section was available in 37 of allpatients (51 percent). The cesarean portion in PIH & PET was higher. Of the 72 newborn patients 16(22.2%)were low in birth weight, and patients with ecclampsy were more likely to experience low birth weight. 35 of72 patients had poor fetal results, including 1.4 percent perinatal and 33.3 percent asphyxiated infants. Only5 (6.5 percent) had complications in maternal outcomes such as strokes, renal eclampsia. All participantsin this study are women who are pregnant and receive prenatal care. WHO normally recommends patientswith an antecedent of antenatal treatment less than 4 times eclampsia. In patients with eclampsia it is morecommon to see low birth weight, pre-term delivery and the complication for prenatal mortality.